Epidemiology of hepatitis B in Poland in 2010-2014 - Marta Estera Kowalska; Paweł Kalinowski; Urszula Jolanta Bojakowska; Marlena Krauze (Kazimierz Wielki University, 2017)
Introduction Hepatitis B virus (HBV) is a liver disease caused by hepatitis B - hepatitis B virus (HBV). This virus has an affinity to liver cells, cause both acute and chronic viral infections of varying severity. Aim The aim of this study was to analysis of incidence of hepatitis B in Poland in 2010-2014. Material and methods The material analyzed in the work were cases of hepatitis B registered in Poland in 2010-2014, taking into account gender, age and place of residence infected published in the form of annual bulletins "Infectious diseases and poisoning in Poland by the National Institutes of Health in Warsaw (NIH). Results In the analyzed period there was an increase in the number of cases of hepatitis B in Poland. Most cases are recorded in the age group above 40 years.